2015
DOI: 10.11648/j.sjph.20150303.17
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Diarrhea Morbidity Among Children Younger than Five Years in the Atwima Nwabiagya District, Ghana: A Cross-Sectional Study

Abstract: This study was conducted in January 2013 to identify risk factors associated with diarrhea morbidity among children younger than 5 years in the Atwima Nwabiagya District, Ghana. A total of 378 households were drawn from four Atwima Nwabiagya District communities in the dry season using a systematic random sampling strategy. Quantitative data was collected from eligible households using interviewer-administered questionnaires and spot-checks. The relationships of socio-demographic, environmental, and behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…This study showed that children to young mothers’ group had higher risk of diarrhea than those of children to older mother’s group. This finding is in line with other studies conducted in low and middle- income countries [ 19 , 20 , 38 , 39 ]. The possible reason might be the greater experience of older women in child care and younger mothers might have less understanding and knowledge about diarrheal disease, mode of transmission and pathogens spread in the household compared to the older ones.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that children to young mothers’ group had higher risk of diarrhea than those of children to older mother’s group. This finding is in line with other studies conducted in low and middle- income countries [ 19 , 20 , 38 , 39 ]. The possible reason might be the greater experience of older women in child care and younger mothers might have less understanding and knowledge about diarrheal disease, mode of transmission and pathogens spread in the household compared to the older ones.…”
Section: Discussionsupporting
confidence: 93%
“…The sanitation indices in Nigeria contributed to the poor human development index, typified by the high infant mortality rate (72.7 per 1000 live births) and under five mortality rate (157 per 1000 live births) [ 6 ]. The above statistics predisposes young children, who tend to defecate in areas where other susceptible children are exposed while learning to walk or playing in their premises, with frequent hands to mouth contacts, thus increasing the prevalence of faeces related diseases in such places and the risk of environmental enteropathy [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Child age [ 5 ] and sex [ 20 ], mother’s age and education [ 4 ], mothers occupation [ 5 ], father’s education [ 21 ], number of under-five children [ 22 ], quality of the main floor material [ 5 ], drinking water source [ 23 ], maternal diarrhea [ 6 ], storing water in containers without lids [ 20 ], use of dippers to draw water from water storage containers [ 9 ], availability of a latrine [ 23 ], method of under-five child stool disposal [ 23 ], improper refuse disposal [ 24 ], availability of handwashing (handwashing is defined as the act of cleaning one’s hands to remove soil, grease, microorganisms, or other unwanted substances) facility [ 14 ], handwashing before preparing food and before eating food [ 8 ], before feeding a child [ 13 ], handwashing after eating and after contact with child feces [ 13 ], visible feces in the compound [ 7 ], and visible feces on the latrine slab [ 7 ] were the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…It is defined as the passage of three or more loose or liquid stools per day [3]. Several studies identified the following risk factors for under-five diarrhea: mother's/guardian's age, education, and occupation [4,5]. Similar studies detected predisposing factors such as maternal history of recent diarrhea, lack of latrines, age of the child [6], and absence of refuse disposal facilities [7] in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%